Handbook of Lubrication and Tribology. - Bruce, Robert W. (CRC Press, 2012)
Since publication of the first edition of this bestselling handbook, energy, s rising costs and its impact on the environment have increased the significance of tribology. This updated and expanded edition provides a condensed treatment of the most essential information surrounding this topic. With contributions by some of the foremost experts in the areas covered, the book summarizes established knowledge and practices and including references for more detailed study.